Prognostic value of lymphocyte-to-monocyte ratio in acute ischemic stroke: a systematic review and meta-analysis - Tian, Chengli; Yang, Yilin; Wan, Jun; Wang, Ran; Zhou, Ke; Li, Yuanli; Guo, Wenlong; Li, Huijun; Zhang, Yu (Frontiers in Neurology, 2025)
BackgroundThe findings from studies exploring the prognostic relevance of the lymphocyte-to-monocyte ratio (LMR) in individuals with acute ischemic stroke (AIS) have shown variability. We aimed to conduct a meta-analysis to determine the prognostic significance of LMR in this patient population.MethodsWe carried out a meta-analysis utilizing information from major databases, including PubMed, Embase, and Web of Science until October 26, 2024. Effect sizes, represented as odds ratios (ORs) along with their corresponding 95% confidence intervals (CI), were synthesized employing a random-effects model in Review Manager Version 5.4. To investigate possible sources of variability, we conducted subgroup analyses. Additionally, publication bias was assessed through the use of a funnel plot. Poor functional outcome at 3 months, as indicated via a modified Rankin Scale score of ≥3, was the main outcome. A moderate to severe stroke, determined by a National Institutes of Health Stroke Scale score of ≥6, was the secondary outcome.ResultsSix trials totaling 1,225 individuals were included in our analysis. In AIS patients, we discovered a significant correlation between lower LMR and poorer functional outcome at 3 months, with an OR of 0.63, 95% CI of 0.49 to 0.80, and a p-value of 0.0002. Additionally, lower LMR may be associated with developing moderate to severe stroke, with an OR of 0.89 (95% CI: 0.82–0.97; p = 0.008). In subgroup analyses with an LMR cutoff, a significant association was observed between lower LMR and greater functional impairment in AIS patients, with an odds ratio of 0.74 (95% CI: 0.62–0.88; p = 0.0005) for LMR ≥ 3 and 0.54 (95% CI: 0.47–0.61; p < 0.00001) for LMR < 3. Additionally, when country-stratified, Asian continued to have a significant correlation between worse functional outcome and lower LMR (OR 0.62, 95% CI: 0.50–0.77, p < 0.0001).ConclusionThis meta-analysis indicated that LMR was a prognostic factor for clinical outcomes in AIS patients.